HUBUNGAN ANTARA KEBIASAAAN OLAHRAGA DENGAN KEJADIAN NYERI HAID PRIMER PADA REMAJA - Sugiharti, Rosi Kurnia; Sumarni, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
At the time of puberty is a lot of changes both psychological and biological. Changes in biological development, characterized by the biological youthfulness in the beginning of menstruation (menstruation). Physical disorders are very prominent in menstrual women is primere menstrual pain. Risk factors for primary menstrual pain vary in the first menstruation at a very early age, never gave birth to children, long periods of menstruation, nutritional status, smoking, exercise habits, stress. Based on preliminary study obtained from the interview on 25 female students of STIKES Harapan Bangsa Purwokerto midwifery study program showed that 45% said mild pain, 40% moderate pain, 15% severe pain. The purpose of this study was to determine the relationship between exercise habits with the incidence of primary menstrual pain at teens. The type of research used is analytic correlation with case study case control design. Samples using purposive sampling. Data were analyzed with frequency distribution and Chi Square. The results showed that there is a relationship between exercise habits with the incidence of primary menstrual pain in adolescents which is indicated by the value of p value 0.02.Keywords: exercise habits, primary menstrual pain events, adolescents